2012
DOI: 10.1002/term.529
|View full text |Cite
|
Sign up to set email alerts
|

Development of endothelium-denuded human umbilical veins as living scaffolds for tissue-engineered small-calibre vascular grafts

Abstract: Tissue-engineered small-calibre vessel grafts may help to alleviate the lack of graft material for coronary and peripheral bypass grafting in an increasing number of patients. This study explored the use of endothelium-denuded human umbilical veins (HUVs) as scaffolds for vascular tissue engineering in a perfusion bioreactor. Vessel diameter (1.2 ± 0.4 mm), wall thickness (0.38 ± 0.09 mm), uniaxial ultimate failure stress (8029 ± 1714 kPa) and burst pressure (48.4 ± 20.2 kPa, range 28.4-83.9 kPa) were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…[18][19][20]22 Given the growing body of literature supporting the central importance of mechanobiological responses in vascular biology and the development of vascular disease, we have begun to characterize the evolving biomechanical properties of TEVGs in the hope of identifying roles of mechanobiological processes in neovessel formation, which is complex and dynamic. In native blood vessels, vascular cells respond to changes in the biomechanical environment by remodeling their ECM to promote mechanical homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20]22 Given the growing body of literature supporting the central importance of mechanobiological responses in vascular biology and the development of vascular disease, we have begun to characterize the evolving biomechanical properties of TEVGs in the hope of identifying roles of mechanobiological processes in neovessel formation, which is complex and dynamic. In native blood vessels, vascular cells respond to changes in the biomechanical environment by remodeling their ECM to promote mechanical homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, biomechanical characterization of TEVGs has been largely limited to characterization of the burst pressure and suture retention strength of the TEVG scaffold. [18][19][20] These critical parameters must be evaluated to determine the clinical utility of any TEVG scaffold and we have previously measured these parameters for our scaffold. 6 Nevertheless, given our successful clinical experience using this TEVG in the Fontan circulation, which demonstrates the lack of aneurysmal dilation or rupture up to 10 years after implantation, it is time to take the next step and move beyond a basic mechanical characterization and into a more sophisticated analysis so that we can begin to understand better the complex, dynamic mechanobiological processes.…”
mentioning
confidence: 99%
“…In order to prepare endothelium‐denuded HUVs, endothelial cells were destroyed by dehydration, as described previously (Hoenicka et al ., ). In brief, the vessels were perfused with carbogen at 60 ml/min for 10 min and then rinsed thoroughly with culture medium.…”
Section: Methodsmentioning
confidence: 97%
“…We have previously investigated human umbilical veins (HUVs) as a source for TEBV and demonstrated that endothelium‐denuded HUVs can be seeded with autologous cells from CABG patients to form a confluent and flow‐resistant neoendothelium (Hoenicka et al ., , , ). The present study was undertaken to investigate the utility of decellularized HUV as scaffolds for vascular tissue engineering and to compare these two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Dies gelang durch Perfusion mit Carbogen (95 % Sauerstoff , 5 % Kohlendioxid). Weiterhin wurde ein Perfusionsbioreaktor benutzt, um durch Rotation während der Besiedelung die Gefäße auf dem gesamten Umfang mit Endothelzellen zu besiedeln und um die Strömungsresistenz des Neoendothels zu über-prüfen[ 44 ] . Schließlich konnte gezeigt werden, dass auch Endothelzellen aus der V. saphena von Patienten mit Koronarer Herzkrankheit auf diesem Scaff old ein strömungsresistentes Neoendothel ausbilden ( • ▶ Abb.…”
unclassified